Golden years - understanding the New Zealand Superannuation Fund - Matthew Bell (New Zealand Government, The Treasury, 2021)
The New Zealand Superannuation Fund (NZSF) is one of New Zealand's largest publicly-owned financial assets. Its primary purpose is to act as an inter-generational tax smoothing vehicle, in order to assist future taxpayers cover the cost of providing the public pension, New Zealand Superannuation (NZS). New Zealand's ageing population structure will, in the absence of any changes to pension settings, lead to a significant lift in NZS expenditure as a percentage of gross domestic product (GDP) over the next few decades. The paper includes an explanation of the reasons behind why this demographic change is occurring and will continue to unfold over the foreseeable future. The paper contributes a comprehensive analysis of the NZSF's role in New Zealand's public finances. This includes descriptions and modelling of NZS and the NZSF, explanations of the mathematical relationships behind the NZSF's legislated contribution rate formula, and a brief history of the NZSF. Future outcomes for the NZSF's size and role in helping to fund NZS, depending on scenarios that vary the evolution of NZS relative to GDP, are illustrated and explained. How and why projections related to the NZSF have changed over time is also analysed and explained, including what factors have had the most influence on these changes. The paper does not comment on the merits of policy decisions that have been made in regard to either NZS or the NZSF. That is not the paper's purpose, outside of covering any aspects of these in regard to how the NZSF has evolved or may evolve in future, or how its logic operates.
Keywords: C20; G17; H55; 330; Single Equation Model; Financial Forecast; Old Age Assistance; Public Pension; Pay as You Go